Desain Taman dan Ruang Baca Anak di Komplek Timah Timur, Cimanggis - Depok - Andrey Caesar Effendi; Danang Harito Wibowo (Prodi Arsitektur Universitas Matana, 2023)
The housing complex, which was built in 1976 for Timah District Court employees, is located in the Depok city area, named Komplek Timah, which is the earliest housing in the Depok city area. The housing complex is divided into two, namely the West Tin Complex and the East Tin Complex. In PKM activities by designing a children's garden and reading room located in the East Timah Complex. The age of the housing which is more than 45 years old has resulted in the neglect of several existing social and public facilities, such as the East Tin Complex in Block EE which is the location of PKM this semester. The purpose of this PKM is to redesign the function of the social and public facilities in the East Timah complex area, which is currently not being used for anything and is left neglected. The design method used is to go directly to the field and ask local administrators so that factual data can be obtained in the field, then students and lecturers begin to define functions and design the social and public facilities. The Matana Architecture Study Program is trying to carry out PKM activities in the form of consulting and designing one of the social and public facilities in this housing area which is often used by the local community every day. This activity involves students of classes 2019 at Matana University as well as a place for them to apply the knowledge they have gained from the Site Design Studio course.